Connection between diffusion coefficient and thermal conductivity of a metal matrix composite; IOP Conference Series: Materials Science and Engineering; Vol. 175 : Competitive Materials and Technology Processes (IC-CMTP4) - Anisimova M. A. Mariya Aleksandrovna (2017, 2017)
Title screen